1984
DOI: 10.1002/ana.410150403
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal intranuclear inclusion disease in identical twins

Abstract: A pair of female identical twins exhibited slurred speech, nystagmus, and oculogyral spasms starting at age 11. The patients then had episodic rage, extrapyramidal and lower motor neuron abnormalities, and grand mal seizures, but retained largely normal intelligence, until death at age 21. Severe loss of nigral and craniospinal motor neurons was noted postmortem. Round, eosinophilic, autofluorescent inclusion bodies, 3 to 10 microns in diameter, were observed in the nuclei of most nerve cell types of the centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
47
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 13 publications
2
47
0
Order By: Relevance
“…Furthermore, we reported that, in this study, tremor, rigidity and general convulsions were rarely observed in adult-onset NIID (Table 2), and these manifestations were frequently reported in infantile and juvenile NIID cases (Sung et al , 1980; Haltia et al , 1984; Funata et al , 1990; Sloane et al , 1994; O'Sullivan et al , 2000; Paviour et al , 2005). Clinical features of infant, juvenile and adult NIID are different, but some clinical manifestations are common to them.…”
Section: Discussionsupporting
confidence: 49%
“…Furthermore, we reported that, in this study, tremor, rigidity and general convulsions were rarely observed in adult-onset NIID (Table 2), and these manifestations were frequently reported in infantile and juvenile NIID cases (Sung et al , 1980; Haltia et al , 1984; Funata et al , 1990; Sloane et al , 1994; O'Sullivan et al , 2000; Paviour et al , 2005). Clinical features of infant, juvenile and adult NIID are different, but some clinical manifestations are common to them.…”
Section: Discussionsupporting
confidence: 49%
“…[2][3][4]9,12,27 Sensory symptoms have attracted attention less frequently, although varying degrees of dorsal column fiber loss in the spinal cord have been observed in many autopsy cases. 3,4,[6][7][8][9]11,12 The pathologic evidence suggests that peripheral sensory involvement probably is typical despite a paucity of sensory symptoms in most reported patients. NIHID previously has been described as a disease involving the central rather than peripheral nervous system, since most patients reported so far have shown mainly CNS symptoms except for intestinal pseudoobstruction and some other autonomic manifestations.…”
Section: Discussionmentioning
confidence: 98%
“…2,[4][5][6][7][8][9][10][12][13][14][15]19,21,24,27 However, nerve conduction was relatively well preserved in most patients in spite of EMG evidence of chronic denervation [5][6][7]14,24,27 ; this suggested axonal impairment predominating over demyelination. Muscle atrophy and hyporeflexia also have been reported previously in some patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The enteric nervous system is only involved in some patients so gastrointestinal manifestations are not always seen. Most cases are sporadic but familial cases have been reported [Schuffler et al, 1978;Haltia et al, 1984;Kimber et al, 1998;Zannolli et al, 2002]. In 1998, Kimber et al reported monozygotic female twins with neurogenic limb weakness, ataxia, and dysarthria and two adult sons of one of the twins with similar manifestations.…”
Section: Discussionmentioning
confidence: 99%